MAPK-activated protein kinase 2 is associated with poor prognosis of glioma patients and immune inhibition in glioma - Sun, Jinmin; Wu, Sicheng; Zhao, Wenyu; Xue, Senrui; Zhang, Lei; Ren, Jing (Frontiers in Oncology, 2024)
Effective therapeutic method to noticeably improve the prognosis of glioma patients has not been developed thus far. MAPK activated protein kinase 2 (MAPKAPK2) is a serine/threonine kinase which is involved in tumorigenesis, tumor growth, metastasis, and the inflammatory process. The clinical significance and molecular function of MAPKAPK2 in glioma remain unclear. MAPKAPK2 expression in glioma tissues was detected by immunohistochemistry and showed that MAPKAPK2 was not only aberrantly upregulated in glioma tissues but also correlated with poor clinical characteristics. Moreover, MAPKAPK2 was prevalent in isocitrate dehydrogenase (IDH) wildtype and 1p/19q non-codeletion gliomas cohorts and predicted poor prognosis of glioma patients. A prognostic nomogram was constructed to predict the survival risk of individual patient. We performed the function and pathway enrichment analysis of MAPKAPK2 which showed MAPKAPK2 may be involved in cell proliferation, cell migration, DNA damage repair and immune regulation in glioma. Single-cell RNA sequencing data showed MAPKAPK2 was mainly enriched in microglia/macrophages and malignant tumor cells. Flow cytometry was used for cell cycle and apoptosis detection. The ability of cell proliferation and migration was analyzed by CCK8 and cell migration assay respectively. Further investigation into cellular function revealed that inhibiting MAPKAPK2 suppressed the proliferation and migration of glioblastoma cells in vitro. The inhibition of MAPKAPK2 significantly induced the G1 cell cycle arrest and cell apoptosis of glioblastoma multiforme (GBM) cells. Consistent with the enriched function of MAPKAPK2 in immune regulation, MAPKAPK2 was correlated with immune cells infiltration in glioma tissues. Mechanistically, a series of immune regulators, immunomodulatory chemokines and chemokines receptors were positively correlated with MAPKAPK2 expression. Thus, our findings provide evidences of the clinical relevance of MAPKAPK2 in prognosis evaluation of glioma patients and highlight the underlying significance of MAPKAPK2 in glioma therapy.